2019
DOI: 10.1186/s13048-019-0555-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin and Exenatide on insulin resistance and AMPKα-SIRT1 molecular pathway in PCOS rats

Abstract: Aims This study was designed to evaluate the protective effects of AMPKα and SIRT1 on insulin resistance in PCOS rats, and to illuminate the underlying mechanisms. Methods An in vitro PCOS model was established by DHEA (6 mg/(100 g•d)), and the rats were randomly divided into the metformin group (MF group, n = 11), the exenatide group (EX group, n = 11), the PCOS group (n = 10), and the normal control group (NC group, n = 10). The MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…In our previous study [7,8], insulin resistance in PCOS rats was associated with the AMPKα-SIRT1 pathway. Furthermore, in our newly study showed that both EX and MET could improve the reproductive and endocrine functions of PCOS mice via the AMPKα-SIRT1 pathway, which may be the molecular mechanism for IR in PCOS and could possibly serve as a therapeutic target [9].…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…In our previous study [7,8], insulin resistance in PCOS rats was associated with the AMPKα-SIRT1 pathway. Furthermore, in our newly study showed that both EX and MET could improve the reproductive and endocrine functions of PCOS mice via the AMPKα-SIRT1 pathway, which may be the molecular mechanism for IR in PCOS and could possibly serve as a therapeutic target [9].…”
Section: Introductionmentioning
confidence: 66%
“…It has been con rmed that MET and EX, extensively applied in metabolic diseases such as T2DM, metabolic syndrome, cardiovascular disease and PCOS, improved patients 'metabolic imbalance and protect patients from corresponding injury. We have investigated the interrelationship between these two drugs and AMPK-SIRT1 pathway in PCOS rat model ovaries, the improved ovarian reservation function has been seen in PCOS rats when intervened by EX or MET [9]. And now, this paper just focused on another side of the same study, the effect of EX on the endometrium of PCOS rat models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TXNIP knockout mice had improved insulin sensitivity and increased glucose uptake in both adipose and skeletal muscle [39]. In PCOS, metformin improved insulin resistance in a PCOS rat model via an AMPK alpha-SIRT1 pathway [44].…”
Section: Insulin Resistancementioning
confidence: 98%